SINDROM POSTERIOR REVERSIBLE ENCEPHALOPATHY - Cut Diana Maya Theresa,* Alfansuri Kadri* (Neurona Majalah Kedokteran Neuro Sains, 2015)
REVERSIBLE ENCEPHALOPATHY SYNDROME PRES IS A RARE AND REVERSIBLE SYNDROME WITH MANY ETIOLOGIES AND DIAGNOSED BASED ON CLINICALRADIOLOGICAL ABNORMALITIES THE MAIN CAUSES INCLUDE HYPERTENSION CYTOTOXIC MEDICATION PREECLAMPSIA OR ECLAMPSIA AUTOIMMUNE AND SYSTEMIC DISEASES